Cytoprotective Mechanisms of DJ-1: Implications in Cardiac Pathophysiology - James N. Tsoporis; Ioannis-Alexandros Drosatos; Sahil Gupta; Hajera Amatullah; Shehla Izhar; Claudia C. dos Santos; Vasileos Salpeas; Angelos G. Rigopoulos; Ioannis K. Toumpoulis; Andreas S. Triantafyllis; Eleftharios Sakadakis; Nikolaos Kavantzas; et al. (Molecules, 2021)
DJ-1 was originally identified as an oncogene product while mutations of the gene encoding DJ-1/PARK7 were later associated with a recessive form of Parkinson’s disease. Its ubiquitous expression and diversity of function suggest that DJ-1 is also involved in mechanisms outside the central nervous system. In the last decade, the contribution of DJ-1 to the protection from ischemia-reperfusion injury has been recognized and its involvement in the pathophysiology of cardiovascular disease is attracting increasing attention. This review describes the current and gaps in our knowledge of DJ-1, focusing on its role in regulating cardiovascular function. In parallel, we present original data showing an association between increased DJ-1 expression and antiapoptotic and anti-inflammatory markers following cardiac and vascular surgical procedures. Future studies should address DJ-1’s role as a plausible novel therapeutic target for cardiovascular disease.